MY PLATE CONTENT CONCEPT BY INDONESIA IN PEOPLE WITH DIABETES MELITUS: Received: 17th October 2023; Revised: 24th October 2023, 06th November 2023; Accepted: 28th November 2023 - Ramadana Br Bangun, Yana Lestari; S. Nasution , Elan Virginia; Sarumpaet, Hafni Pratiwi; Anggesti, Indi; Utami Ningsih, Winda; Ismah, Zata (LIFE: International Journal of Health and Life-Sciences, 2023)
The metabolic sondition known as Diabetes melitus (DM) is chronic and complex. Several risk factors for Diabetes mellitus include age, degree of education, tobacco smoking, and BMI. In Indonesia, the incidence of Diabetes Mellitus has increased in every year. Impaired absorption of insulin in people with Diabetes mellitus requires sufferers to be able to pay more attention to many things in fulfilling daily nutrition. The contents of my plate can be a choice of eating concepts for diabetics. This research is to find out how the concept of eating with the contents of my plates for people with DM. This study use study literature method, where the researcher collects and quotes the necessary information from various sources of scrutiny. From this research, metabolic syndrome in Diabetes is a condition in which a person experiences hyperglycemia. Liquid glucose and insulin in patients can no longer function and carry out their work in the body as they should. The nutritional intake of people with Diabetes mellitus must be considered, because if not this disease can become a disease that can cause other diseases. This can be overcome by dieting for sufferers, dieting in the sense of maintaining the sufferer's daily eating habits each day which in this case can be done with the concept of my plate contents. From this study it can be seen that people with Diabetes mellitus have a high risk of contracting other co-morbidities. Individuals with Diabetes melitus are at significant risk. With a good lifestyle, the risk factors for other co-morbidities can be minimized. This makes it important to pay attention to food consumption with the concept of what's on my plate for diabetics.